Multicomponent dynamics in amorphous ice studied using X-ray photon correlation spectroscopy at elevated pressure and cryogenic temperatures - Aigerim Karina; Hailong Li; Tobias Eklund; Marjorie Ladd-Parada; Bernhard Massani; Mariia Filianina; Neha Kondedan; Andreas Rydh; Klara Holl; Ryan Trevorah; Simo Huotari; Robert P. C. Bauer; et al. (Communications Chemistry)
Abstract Knowing the pressure dependence of glass forming liquids is important in various contexts. Here, we study the case of supercooled water, which has at least two different amorphous states with different densities. The pressure dependencies of the two glass transitions are predicted to show opposite behaviour, crossing in the P-T plane at elevated pressure. The experimental identification of the glass transition at elevated pressure and cryo-conditions is technically difficult. Moreover, in the case of amorphous ices, the glass transition is interrupted by crystallization, which makes it even more challenging. We show the feasibility of performing X-ray photon correlation spectroscopy experiments at elevated pressure using a diamond anvil cell at cryogenic temperatures. We observe two dynamic components when approaching the glass transition temperature. For high-density amorphous ice at a pressure of around (0.08 ± 0.02) GPa we determine the glass transition to be at higher temperatures compared to ambient conditions.